Analisis Kepatuhan Minum Obat Pada Pasien Lansia Hipertensi Di Puskesmas Tanjung Sakti Pumi Tahun 2023 - Yolanda Budiarti; Ali Harokan; Lilis Suryani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Hypertension is high blood pressure where the systolic blood pressure is 140 mmHg or the diastolic blood pressure is 90 mmHg. This study aims to determine the factors associated with medication adherence in elderly hypertensive patients at the Tanjung Sakti Pumi Health Center in 2023. The design of this study was a quantitative cross-sectional approach. The population in this study is all patient visits at the Tanjung Sakti Pumi Health Center in 2022, namely 1166 respondents. Sampling using slovin theory. The sample in this study amounted to 92 people. How to take samples using purposive sampling. This research was carried out from 18 May 2023 to 29 May 2023. Data collection used a questionnaire. Bivariate data analysis using the Chi-Square test.The results showed that there was a relationship between age (p value 0.001), knowledge (p value 0.032), family support (p value 0.0370 with medication adherence in elderly hypertensive patients at the Tanjung Sakti Pumi Health Center in 2023. There was no gender relationship (p value 1.00), history of hypertension (p value 0.63) and history of comorbidities with adherence to taking medication in elderly hypertensive patients at the Tanjung Sakti Pumi Health Center in 2023.There is a need for efforts to increase knowledge as well as conduct education, outreach and strengthen the elderly Posyandu in the Puskesmas area.